PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA UNIVERSITAS BATANGHARI - Reni Devita (Universitas Batanghari Jambi, 2015)
The influence of leadership and employee performance in University of Batanghari Jambi should be adapted with necessary that must be filled and level of different necessary to every employee, so as different performances happens in achivement. The condition is the employee often came late for work, act like passive and positive to work, not on time for finishing the job and the half employee still exist to out from their assignment in office hours without legal information.The research method in used is descriptive method and verifikatif. The sample is total sampling as 80 person. Field The result from this research show that leadership and employee performance in University of Batanghari Jambi with good criteria. The empirical findings indicates that in order to improve employee performance, so part of rector should be considering the factors that employee performance affect, such as leadership. Since knowing the relationship affect used as reference for designing strategies to increase employee performance.keywords : leadership, performance, employee